Perancangan Sistem Informasi Persewaan Alat Mendaki Berbasis Web pada Summit Kalcer dengan Metode Waterfall - Nabilla Putri Sari Fatikhah; Muhammad Abdullah; Nopi Doni Romadhon; Musahabib Nugroho (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Rock climbing and hiking are outdoor activities that continue to gain popularity among various age groups. However, not all enthusiasts are fully equipped or prepared with the necessary gear. Renting hiking equipment becomes a practical and cost-effective alternative for climbers, especially beginners. Unfortunately, many rental service providers still rely on manual systems, which often lead to inefficiencies such as booking errors, lack of real-time inventory updates, and delays in transaction processing. This study aims to design and develop a web-based information system for renting hiking equipment at Summit Kalcer, using the Waterfall method. The system is designed to address the shortcomings of manual processes by providing real-time information on equipment availability, streamlining the booking process, and enabling admin validation after payment confirmation. The Waterfall approach includes several sequential stages: requirements analysis, system design, implementation, testing, deployment, and maintenance. The resulting web-based system allows users to rent equipment flexibly, anytime and anywhere, without the need to visit the rental location physically. Customers can browse available tools, make reservations, and upload payment proof through an intuitive interface. On the administrative side, the system supports efficient data management and transaction verification, thereby reducing the risk of human error and enhancing overall service quality. By implementing this system, Summit Kalcer can improve its service efficiency, customer satisfaction, and operational productivity. This research demonstrates that digitalizing the rental process not only improves convenience for users but also provides a scalable solution for rental businesses looking to adapt to modern technological demands.